2013
DOI: 10.1021/ef301694x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Torrefaction on Bio-oil Upgrading over HZSM-5. Part 1: Product Yield, Product Quality, and Catalyst Effectiveness for Benzene, Toluene, Ethylbenzene, and Xylene Production

Abstract: A three-step bio-oil production process involving torrefaction pretreatment (at 225, 250, or 275°C with a 20 min hold time), pyrolysis (at 500°C with two heating rates), and secondary catalytic processing over 450, or 500°C ) was studied to determine process effects, particularly of torrefaction, on the yield of liquid and aromatic hydrocarbons and the quality of upgraded bio-oil. When bio-oils derived from torrefied biomass were catalytically cracked, average yields (%, w/w of feed) of reactor char (100% r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…Chen et al also observed S and N content increases in the torrefied sawdust in relation to raw feedstock. Hilten et al also stated important increases in N contents in torrefied pine chips.…”
Section: Resultsmentioning
confidence: 94%
“…Chen et al also observed S and N content increases in the torrefied sawdust in relation to raw feedstock. Hilten et al also stated important increases in N contents in torrefied pine chips.…”
Section: Resultsmentioning
confidence: 94%
“…One of the greatest disadvantages of bio-oil is its high oxygen content. This high oxygen content requires an energy and hydrogen-rich catalytic upgrading process . Many of the oxygen-rich products are generated from the hemicellulose and cellulose fractions.…”
Section: Introductionmentioning
confidence: 99%
“…The lignin fraction does contribute to the oxygen content, but because of the nature of the phenolic ring, the lignin fraction contributes more significantly to the carbon content of the bio-oil. Phenolic structures are easier to upgrade than carbohydrate-derived bio-oil compounds using catalytic hydrotreatment, have higher carbon-to-oxygen ratios, and can therefore produce a more energy-dense biofuel product …”
Section: Introductionmentioning
confidence: 99%
“…The mass yield from torrefaction usually is less than 1. Therefore, even though there is some biomass energy loss during torrefaction due to the loss of volatile organic material (e.g., between 3-17% as reported by Hilten et al, 2013a), the energy yield usually is greater than one because of the reduced torrefied product mass. Hilten et al (2013b) also reported that the net thermal process efficiency is defined as the energy yield in the torrefied products divided by the total energy input (e.g., the energy content of the feedstock plus energy added to the heat and run the torrefaction process).…”
mentioning
confidence: 99%